Gender Inequality in Household Chores and Work-Family Conflict - Cerrato, Javier; Cifre, Eva (Frontiers in Psychology, 2018)
The fact that the permeability between family and work scopes produces work-family conflict (WFC) is well established. As such, this research aims to check whether the unequal involvement in household chores between men and women is associated with increased WFC in women and men, interpreting the results also from the knowledge that arise from gender studies. A correlational study was carried out by means a questionnaire applied to 515 subjects (63% men) of two independent samples of Spanish men and women without emotional relationship, who lived with their heterosexual partner. As expected, results firstly show unequal involvement in household chores by women and men as it is higher in women that in men, and the perception of partner involvement is lower in women that in men. Secondly, those unequal involvements relate differently to men and women on different ways of work-family interaction. They do not increase WFC in women comparing to men, although there are tangentially significant differences in work conflict (WC) and statistically significant in family conflict (FC). However, perception of partner involvement on household chores increases WFC both in men and in women but not WC nor FC. Nevertheless, increase on marital conflict (MC) by domestic tasks neither affect in a significant way WFC in women nor in men, but increase WC in both women and men and FC only in women. Results also confirm that subject involvement on household chores is not a significant predictor of WFC in women nor in men, and that MC by domestic tasks is a statistically significant predictor in women of WFC and FC, but not in men. Thus, results show that traditional gender roles still affect the way men and women manage the work and family interaction, although the increased WFC due to involvement in housework is not exclusive to women, but also occurs in men. Personal and institutional recommendations are made on the basis of these results to cope with these conflicts.